KARAKTERISASIKERAMIK TERMISTOR Fe203:lmTi HASIL SINTER DAN PERLAKUAN PANAS - Syarif, Dani Gustaman (MESIN, 2007)
This studywas done to know the effect ofTi02 addition on the characteristics qfFe203ceramics and the effect of a heat treatment at low temperature on the electrical characteristics ofFe203:lmTi ceramics including the mechanism ofits change as well. The Fe203:lmTi ceramics wereproduced bysintering some green pellets from mixture of 99.9 mole %Fe203 and I mole %Ti02 at1200Â°C for I hour in air. A heat treatment was carried out at 75(fC in air with a cooling rate ofTC/minute. Electrical resistivity ofthe ceramics was measured at different temperatures before andafter heat treatment. X-ray diffraction (XRD) analysis was done to know the crystal structure of theceramics and phases formed therein. It was known that the crystal structure of the Fe203 andFe203:lmTi ceramics was thesame i.e. that similar to hematite. The electricalcharacteristics showedthat the room temperature resistivity (psn) of the Fe203 ceramics drastically decreased with I mole %Ti02 addition and showedthat the (pSR) oftheFe203:lmTi ceramics increased significantly while thevalue of the thermistor constant (B) relatively did not change, after the heat treatment. The increase of(psn) after the heat treatment was caused by lessformation of oxygen vacancies which behave as theelectron sourcefor conduction band.